Abrogation in the Holy Qur’an is an intellectual, interpretive, linguistic study (Islamic Sciences Journal, 2024)
ABSTRACTPraise be to God, Lord of the Worlds, and prayers and peace be upon our master Muhammad and upon his family and all his companions: Abolition is a dangerous matter for the life of society, individuals and groups, because it is following the path of falsehood and straying from the path of truth. Therefore, the Holy Qur’an strongly warned against it, and explained its various forms and types, and mentioned the most important reasons for falling. In it are disbelief, the worship of the tyrant, and following the self that leads to evil and desires, love of the world, prestige, injustice, and tyranny. Likewise, the purified Sunnah of the Prophet came in harmony with the Holy Qur’an to explain the effects of wrongdoing and its dangers. The greatest mission of the Messengers, peace be upon them, and upon our Prophet, the best prayers and peace be upon him, is to bring people out of the darkness of wrongdoing into the light of faith and guidance. Therefore, I studied the falsehood in the Holy Qur’an, linguistically, interpretatively, and intellectually, to know its truth and to beware of following its false path. I also explained the role of the preachers, who are the heirs of the prophets, peace be upon them, in carrying the message and advising people not to follow the falsehood, and calling them to follow the path of maturity and faith.
Keywords: Abrogation, the Holy Qur’an, linguistic, interpretive, intellectual